Impedance-based stability analysis of DAB converters with single-, double-, or cooperative triple-phase-shift modulations and input LC filter - Feng, Fan (2022)
The impedance-based criterion has turned out to be a very effective tool for the stability analysis of the dual active bridge (DAB) converter with its input LC filter. While the input impedance of the DAB converter is highly dependent on the modulation methods, the influences of the modulation methods on the input impedances of the DAB converters are still not clear. To close this gap, three typical modulation methods of DAB converters, traditional single-phase-shift (SPS), dual-phase-shift (DPS) and the emerging cooperative triple-phase-shift (CTPS) modulation, are studied in this paper. First, the full-order input impedance models of the DAB converter with these modulation methods are derived for the first time. Second, based on the developed models, the impacts of these modulation schemes on the DAB input impedances are revealed. An interesting phenomenon is found that the open-loop impedances of SPS-DAB and DPS-DAB converters present the characteristics of the parallel-connected inductor and capacitor, while the open-loop impedance of CTPS-DAB converter presents the resistor characteristics. Third, the optimal modulation scheme for system stability is investigated. Finally, the theoretical analysis has been validated by the experimental results.